Bioaugmented Mixed Culture by Clostridium aceticum to Manipulate Volatile Fatty Acids Composition From the Fermentation of Cheese Production Wastewater - Atasoy, Merve; Cetecioglu, Zeynep (Frontiers in Microbiology, 2021)
Production of targeted volatile fatty acid (VFA) composition by fermentation is a promising approach for upstream and post-stream VFA applications. In the current study, the bioaugmented mixed microbial culture by Clostridium aceticum was used to produce acetic acid acetic acid dominant VFA mixture. For this purpose, anaerobic sequencing batch reactors (bioaugmented and control) were operated under pH 10 and fed by cheese processing wastewater. The efficiency and stability of the bioaugmentation strategy was monitored by production and composition of VFA, the quantity of C. aceticum (by qPCR) and bacterial community profile (16S rRNA Illumina Sequencing). The bioaugmented mixed culture significantly increased acetic acid concentration in the VFA mixture (from 1170±18 mgCOD/L to 122±9 mgCOD/L) compared to the control reactor. Furthermore, the total VFA production (from 1254±11 mgCOD/L to 5493±36 mgCOD/L) was also enhanced. Nevertheless, the bioaugmentation couldn’t shift the propionic acid dominancy in the VFA mixture. The most significant effect of bioaugmentation on the bacterial community profile was seen in the relative abundance of Thermoanaerobacterales Family III. Incertae Sedis, its relative abundance increased simultaneously with the gene copy number of C. aceticum during bioaugmentation. These results suggest that there might be a syntropy between species of Thermoanaerobacterales Family III. Incertae Sedis and C. aceticum. The cycle analysis stated that 6 hours was adequate retention time to have the same acetic acid and total VFA production efficiency instead of 24 hours. Despite that biobased acetic acid production is widely applicable and economically competitive with petroleum-based production, this study has the potential to enable a new approach: produced acetic acid dominant VFA can be replaced by external carbon source for different processes (such as denitrification) in WWTPs. In this way, higher treatment efficiency at WWTPs will be obtained by recovered substrate from the waste streams that promotes a circular economy approach.